Chronic Neck Pain and Whiplash: A Case-Control Study of the Relationship between Acute Whiplash Injuries and Chronic Neck Pain - Michael D Freeman; Arthur C Croft; Annette M Rossignol; Christopher J Centeno; Whitney L Elkins (Pain Research and Management)
The authors undertook a case-control study of chronic neck pain and whiplash injuries in nine states in the United States to determine whether whiplash injuries contributed significantly to the population of individuals with chronic neck and other spine pain.